2018
DOI: 10.1016/j.thorsurg.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Management of Malignant Lung Entrapment, the Oncothorax

Abstract: Pleural metastasis is a common occurrence in up to 30% of patients with metastatic cancer. When lung entrapment and loculation of fluid occur, treatment is more difficult and we have named this condition "oncothorax." The malignant adhesions that entrap the lung in an oncothorax are not typically amenable to surgical decortication. The standard approach for managing these patients is to place an indwelling catheter. Other options may include pleurectomy and decortication, intrapleural hyperthermic chemoperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Low grade renal toxicity can occur in as many as 30% of patients with baseline normal kidney function and good performance status after cisplatin HITHOC (36). Typical renoprotective measures including resuscitative fluids and diuretics are given, and sodium thiosulfate may limit systemic absorption of platinumbased HITHOC (11). A recent study of 84 patients receiving intrapleural hyperthermic cisplatin + doxorubicin demonstrated that cytoprotection with perioperative fluid support was associated with fewer and less pronounced renal effects even when given in conjunction with higher concentrations of cisplatin (37).…”
Section: Safety and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low grade renal toxicity can occur in as many as 30% of patients with baseline normal kidney function and good performance status after cisplatin HITHOC (36). Typical renoprotective measures including resuscitative fluids and diuretics are given, and sodium thiosulfate may limit systemic absorption of platinumbased HITHOC (11). A recent study of 84 patients receiving intrapleural hyperthermic cisplatin + doxorubicin demonstrated that cytoprotection with perioperative fluid support was associated with fewer and less pronounced renal effects even when given in conjunction with higher concentrations of cisplatin (37).…”
Section: Safety and Side Effectsmentioning
confidence: 99%
“…In the most common general techniques, a pleurectomy and/or debulking is first performed under general anesthesia, followed by consistent instillation of a cisplatinbased fluid mixture at a temperature range of 42-45 ℃ for 30-90 min (9)(10)(11)(12). Attention to core body temperature maintenance is critical and patients require careful postoperative monitoring to address potential side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown low toxicity and excellent 5-and 10-year survival rates of greater than 80% and 70% respectively. 65,66…”
Section: Management Of Resectable Stage III and Iva Tetmentioning
confidence: 99%